1957
DOI: 10.1113/jphysiol.1957.sp005734
|View full text |Cite
|
Sign up to set email alerts
|

Secretion by the parotid gland of the sheep: the relationship between salivary flow and composition

Abstract: Alterations in the concentrations of sodium and potassium in saliva have been extensively studied and related to the external balance of these ions, and to the level of function of the adrenal cortex. Rather less interest has been shown, however, in the relationship between these concentrations and the degree of activity of the salivary glands manifested by altering rates of flow, and in factors influencing the salivary concentration of anions. Heidenhain (1878) showed an increase in the salt content of dogs'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
40
1

Year Published

1957
1957
1996
1996

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 10 publications
7
40
1
Order By: Relevance
“…Coats and Wright (1957) used electrical stimulation of the parotid nerve to alter the rate of salivary flow, which is another obvious difference· between those experiments and the present investigation. However for the following reasons this difference is unlikely to be the cause of the different results obtained:…”
mentioning
confidence: 75%
See 4 more Smart Citations
“…Coats and Wright (1957) used electrical stimulation of the parotid nerve to alter the rate of salivary flow, which is another obvious difference· between those experiments and the present investigation. However for the following reasons this difference is unlikely to be the cause of the different results obtained:…”
mentioning
confidence: 75%
“…Previous reports have indicated that the relation between salivary flow and chloride concentration tends to be rather unpredictable (Coats and Wright 1957;Kay 1960;Beal 1979). During stimulation of salivary flow rate by acetylcholine infusion, the concentration of chloride fell in five experiments and rose in three.…”
mentioning
confidence: 75%
See 3 more Smart Citations